Factores psicosociales de riesgo asociados a conductas problemáticas en jóvenes infractores y no infractores (2010)
The present study examines the risk factors associated with antisocial and criminal behavior in two groups of adolescents. A group consists of teenagers who are being held in two private institutions for juvenile offenders, and the control group of adolescent's offenders, attending a public school. The sample consisted of 179 adolescents aged between 12 and 18. The sample mean age was 15 years. The results were analyzed with SPSS 15.0. To analyze demographic information and test scores. The results show that adolescents who are being held in two institutions for juvenile offenders have an increased frequency of exposure to risk factors associated with antisocial and criminal behavior in adolescents compared with offenders who attend a public institution, exosystem levels, micro and macro. Abuse, alcohol use and abuse are factors that are exposed in similar proportions the two groups of adolescents and risk factors are most associated with the generation of antisocial behavior and criminal behavior.